Toxicity of a botanical insecticide on Bombus impatiens, Apis mellifera, Chrysoperla carnea and Orius insidiosus - Luna-Cruz, Alfonso; Lomeli-Flores, J. Refugio; Rodríguez-Leyva, Esteban; Tovar-Hernández, Horacio; Vanegas-Rico, Juan Manuel; Murillo-Hernández, Juan Eduardo (Revista Mexicana de Ciencias Agrícolas, 2018)
The indiscriminate use of synthetic insecticides increases the risks of contamination to the environment, damage to health and reduction of populations of beneficial organisms, as well as selection of resistance of pests to these products. Given this scenario, efficient and less harmful alternatives are required for humans and non-target organisms. In this research the acute toxicity of botanical insecticide-acaricide BIODIe® (based on plant extracts of castor bean, chicalote and berberis) was evaluated on two pollinators -bees and bumblebees- and on the predators Chrysoperla carnea and Orius insidiosus, three methodologies were used of exposure: direct contact, residual contact and oral toxicity. The botanical insecticide was slightly toxic to the pollinators and predators studied, and was classified in category 1 of the international biological control organization (IOBC) due to low mortality (<25%). This suggests that this product represents low risks for non-target organisms in their implementation in integrated pest management.